Pengalaman, Motivasi dan Keterlibatan Kerja Terhadap Produktivitas Kerja Pegawai Perusahaan Jasa Surveyor Independen di wilayah Jakarta: Experience, Motivation and Work Involvement on Work Productivity at an Independent Surveyor Service Company in the Jakarta area - Gozali, Ahmad; Sapruwan, Muhammad (MASTER: Jurnal Manajemen Strategik Kewirausahaan, 2023)
Penelitian bermaksud menganalisis pengaruh pengalaman, motivasi dan keterlibatan kerja terhadap produktivitas kerja. Pengalaman, motivasi, dan keterlibatn kerja dapat memberikan jaminan terhadap peningkatan produktivitas kerja. Data penelitian diperoleh dari kuesioner yang diberikan melalui Google Form kepada karyawan pada perusahaan jasa surveyor independen di wilayah Jakarta. Pengambilan sampel menggunakan quota sampling, dimana jumlah sampel dibatasi sampai dengan 115 responden. Statistical Package for the Social Sciences digunakan dalam analisis statistika. Hasil penelitian mampu membuktikan bahwa pengalaman, motivasi dan keterlibatan kerja berpengaruh terhadap produktivitas kerja pada perusahaan jasa surveyor independen. The research intends to analyze the effect of experience, motivation and work involvement on work productivity. Experience can guarantee an increase in work productivity. Motivation in doing work is needed to be able to complete the job well. In addition, work involvement also affects work productivity because work involvement can produce good work productivity. Increased work productivity is needed to achieve the goals set by the company. The research data was obtained from a questionnaire given via Google Form to employees at an independent surveyor service company in the Jakarta area. Sampling using quota sampling, where the number of samples is limited to 115 respondents. The Statistical Package for the Social Sciences was used in statistical analysis. The results of the study are able to prove that experience, motivation and work involvement have an effect on work productivity in independent surveyor service companies.